Chronic infection: as an ecological model for emergence of the chronic obstructive pulmonary disease - Dmitriy V. Alekseev; Artem V. Lyamin; Karim A. Kayumov (Novel Research in Microbiology Journal, 2023)
Chronic infections; emerging as complications of some primary diseases, can hardly be considered as classical infectious processes. Such infections may be caused by the non- traditional pathogenic bacteria; as in the cases of cystic fibrosis; chronic obstructive pulmonary disease (COPD), inflammatory bowel diseases, etc. Emergence of these complications is caused by several disorders in the ecosystem; constituting the human body and its microbiota. It is reasonable to extrapolate some ecological principles of the bacterial community's assembly in the humans; as there is a wide variety of factors affecting this, which can be considered as ecological ones. The human microbiota is formed during changes of the different bacterial succession types; under the influence of stochastic and deterministic ecological processes, in addition to different types of the selection pressure. During certain diseases, such as COPD, the normal course of the bacterial community's formation is disrupted. It is associated with anatomical and physiological defects, which cause changes in the properties of the ecological niche; occupied by the communities (i.e., airways in the case of COPD). Altered niches can be occupied by the virulent microorganisms, which get resource advantage and form new stable community. The severity of such chronic infections is correlated with biological diversity in the communities, which tends to decrease in the more severe cases and in the exacerbations. The aim of this study was to create an ecological model of the chronic infections; through synthesizing the ecological and medical knowledge. This model, such as the COPD; may establish new approach to the chronic infections etiopathogenesis, which enables to get better understanding of the clinical course in these diseases and to propose more effective therapies in the future.